Relative sit‐to‐stand power: aging trajectories, functionally relevant cut‐off points, and normative data in a large European cohort. Issue 4 (3rd July 2021) - Alcazar, Julian; Alegre, Luis M.; Van Roie, Evelien; Magalhães, João P.; Nielsen, Barbara R.; González‐Gross, Marcela; Júdice, Pedro B.; Casajús, Jose A.; Delecluse, Christophe; Sardinha, Luis B.; Suetta, Charlotte; Ara, Ignacio
Abstract: Background: A validated, standardized, and feasible test to assess muscle power in older adults has recently been reported: the sit‐to‐stand (STS) muscle power test. This investigation aimed to assess the relationship between relative STS power and age and to provide normative data, cut‐off points, and minimal clinically important differences (MCID) for STS power measures in older women and men. Methods: A total of 9320 older adults (6161 women and 3159 men) aged 60–103 years and 586 young and middle‐aged adults (318 women and 268 men) aged 20–60 years were included in this cross‐sectional study. Relative (normalized to body mass), allometric (normalized to height squared), and specific (normalized to legs muscle mass) muscle power values were assessed by the 30 s STS power test. Body composition was evaluated by dual energy X‐ray absorptiometry and bioelectrical impedance analysis, and legs skeletal muscle index (SMI; normalized to height squared) was calculated. Habitual and maximal gait speed, timed up‐and‐go test, and 6 min walking distance were collected as physical performance measures, and participants were classified into two groups: well‐functioning and mobility‐limited older adults. Results: Relative STS power was found to decrease between 30–50 years (−0.05 W·kg −1 ·year −1 ; P > 0.05), 50–80 years (−0.10 to −0.13 W·kg −1 ·year −1 ; P < 0.001), and above 80 years (−0.07 to −0.08 W·kg −1 ·year −1 ; P < 0.001). A total of 1129 older women (18%) and 510 older men (16%) presented mobility limitations. Mobility‐limited older adults were older and exhibited lower relative, allometric, and specific power; higher body mass index (BMI) and legs SMI (both only in women); and lower legs SMI (only in men) than their well‐functioning counterparts (all P < 0.05). Normative data and cut‐off points for relative, allometric, and specific STS power and for BMI and legs SMI were reported. Low relative STS power occurred below 2.1 W·kg −1 in women (area under the curve, AUC, [95% confidence interval, CI] = 0.85 [0.84–0.87]) and below 2.6 W·kg −1 in men (AUC [95% CI] = 0.89 [0.87–0.91]). The age‐adjusted odds ratios [95% CI] for mobility limitations in older women and men with low relative STS power were 10.6 [9.0–12.6] and 14.1 [10.9–18.2], respectively. MCID values for relative STS power were 0.33 W·kg −1 in women and 0.42 W·kg −1 in men. Conclusions: Relative STS power decreased significantly after the age of 50 years and was negatively and strongly associated with mobility limitations. Our study provides normative data, functionally relevant cut‐off points, and MCID values for STS power for their use in daily clinical practice.